1998
DOI: 10.1037/0012-1649.34.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Lateral asymmetries in infant melody perception.

Abstract: Two experiments investigated lateral asymmetries in infants' perception of contour-altered and contour-preserved melody changes. In the first study, 40 infants (8.5 months old) of right-handed parents were trained to respond to binaural melody changes with a head turn toward mechanized toy reinforcers. The subsequent test phase included monaural left-ear and right-ear presentations of the familiar melody and of a changed melody. Infants who heard a contour-altered change showed a left-ear advantage, whereas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…82,83 Moreover, eight-month-old infants exhibit a left-ear superiority for contour processing and a right-ear superiority for intervalic processing. 84 Such laterality effects parallel those reported for adults. 85,86…”
Section: Hemispheric Specializationsupporting
confidence: 63%
“…82,83 Moreover, eight-month-old infants exhibit a left-ear superiority for contour processing and a right-ear superiority for intervalic processing. 84 Such laterality effects parallel those reported for adults. 85,86…”
Section: Hemispheric Specializationsupporting
confidence: 63%
“…Earlier studies show autonomy between language and music processing. Newborn infants’ hemispheric dominances differ between language (left hemisphere, Witelson and Pallie 1973 ) and music (right hemisphere, Balaban et al 1998 ). Individuals with a disorder in one domain may have the other domain largely intact (Ullman et al 1997 ; Hébert et al 2003 ; Peretz et al 2003 ; Peretz and Coltheart 2003 ; Racette et al 2006 ; Wilson et al 2006 ; Schlaug et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such integration may occur very early in development. Balaban et al (1998) have shown that the same left-right brain asymmetry in the processing of interval and contour cues in melodies is already present in infancy. In the adult, extraction of both contour and intervals does not require attention either, as electrical brain responses suggest (Tervaniemi 2003, Trainor et al 2002.…”
Section: Pitch Relationsmentioning
confidence: 93%